Human health implication of 900MHz and 1800MHz mobile phones - Kasumawati, Lias; Dayang Azra, Awang Mat; Kuryati, Kipli; Ade Syaheda Wani, Marzuki (IEEE, 2009)
In recent years, there has been increasing public concern about the health implication of Electromagnetic (EM) wave exposures due to the mobile phone. For this reason, various public organizations in the world have been established safety guidelines. This paper focused on the investigation or study of human health effect that cause by the used of 900MHz and 1800MHz mobile phones. For the purpose of the assessment, Finite-Difference Time Domain (FDTD) is used to find the Specific Absorption Rate (SAR) value of mobile phones that absorbed into human head. The minimum SAR value stated by International Commission on Non-Ionization Radiation Protection (ICNIRP) is 4W/kg. When the limit is exceeds, it produces human health effects where it can caused reverse cell membrane polarity, alter brain waves and brain chemistry and damage DNA. This leads to cancer and memory loss. However, mobile phones are designed with low power and operate at high frequency where the value of SAR is lower than the limit that stated by ICNIRP. Other temporary biological or potential human health effects produce by mobile phones are heating, headache, fuzziness, fatigue and nausea. By the way, further studies or researches are needed in order to draw more complete picture of health risks that cause by the use of mobile phones.